Voltage-Gated Sodium Channel in Grasshopper Mice Defends Against Bark Scorpion Toxin - Rowe, Ashlee H. (2013)
Painful venoms are used to deter predators. Pain itself, however, can signal damage and thus serves an important adaptive function. Evolution to reduce general pain responses, although valuable for preying on venomous species, is rare, likely because it comes with the risk of reduced response to tissue damage. Bark scorpions capitalize on the protective pain pathway of predators by inflicting intensely painful stings. However, grasshopper mice regularly attack and consume bark scorpions, grooming only briefly when stung. Bark scorpion venom induces pain in many mammals (house mice, rats, humans) by activating the voltage-gated Na(+) channel Nav1.7, but has no effect on Nav1.8. Grasshopper mice Nav1.8 has amino acid variants that bind bark scorpion toxins and inhibit Na(+) currents, blocking action potential propagation and inducing analgesia. Thus, grasshopper mice have solved the predator-pain problem by using a toxin bound to a nontarget channel to block transmission of the pain signals the venom itself is initiating.